Modulation of Fronto-Striatal Functional Connectivity Using Transcranial Magnetic Stimulation - Alkhasli, Isabel; Sakreida, Katrin; Mottaghy, Felix M.; Binkofski, Ferdinand (Frontiers in Human Neuroscience, 2019)
Background The fronto-striatal network is involved in various motor, cognitive and emotional processes, such as spatial attention, working memory, decision-making and emotion regulation. Intermittent theta burst transcranial magnetic stimulation (iTBS) has been shown to modulate functional connectivity of brain networks. Long stimulation intervals, as well as high stimulation intensities are typically applied in transcranial magnetic stimulation therapy for mood disorders. The role of stimulation intensity on network function and homeostasis has not been explored systematically yet. Objective We aimed to modulate fronto-striatal connectivity by applying iTBS at different intensities to the left dorso-lateral prefrontal cortex (DLPFC). We measured individual and group changes by comparing resting state functional magnetic resonance imaging (rsfMRI) pre-iTBS und post iTBS. Differential effects of individual sub- versus supra-resting motor-threshold stimulation intensities were assessed. Methods Sixteen healthy subjects underwent excitatory iTBS at two intensities (90 % and 120 % of individual resting motor threshold) on separate days. 600 pulses (2 s trains, 8 s pauses, duration of 3 minutes, 20 seconds) were applied over the left DLPFC. Directly before and 7 min after stimulation, task-free rsfMRI sessions, lasting 10 min each, were conducted. Individual seed-to-seed functional connectivity changes were calculated for ten fronto-striatal and amygdala regions of interest with the SPM toolbox DPABI. Results Sub-threshold-iTBS increased functional connectivity directly between the left DLPFC and the left and right caudate, respectively, as well as between the right DLPFC and the left caudate. Indirectly, functional connectivity between the right putamen and the left nucleus accumbens and the left amygdala, respectively, was increased. Supra-threshold stimulation did not change fronto-striatal functional connectivity, but only increased functional connectivity between the left amygdala and the caudate nuclei, as well as the left putamen, respectively. Conclusion A short iTBS protocol applied at sub-threshold intensities was not only sufficient, but favourable in order to increase bilateral fronto-striatal functional connectivity, while minimising side effects. Decreased functional connectivity after supra-threshold stimulation was possibly caused by network homeostatic effects.